2021
DOI: 10.5005/jp-journals-10071-23752
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CT Severity Score and Capillary Blood Oxygen Saturation in Patients with COVID-19 Infection

Abstract: A bstract Background: COVID-19 pneumonia is responsible for the latest pandemic. Usage of pulmonary computed tomography (CT) scan is known to be an important method in the diagnosis of COVID-19. Here, we aimed to evaluate the relationship between CT severity score and capillary blood oxygen saturation in patients with COVID-19 infection. Methods and material: This is a cross-sectional study performed in 2020 on patients with COVID-19 infection. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Another study also confirmed that severe/critical patients with respiratory rate ≥ 30 times/min and SpO2 of 93% or less in a resting state had higher total CT scores than ordinary COVID-19 patients [ 23 ]. Aalinezhad [ 24 ] and Osman[ 25 ] et al also reported higher chest CT score is inversely associated with O2 saturation. Furthermore, a multicenter cohort study demonstrated that consolidation in upper lungs on the initial chest CT of COVID-19 patients was associated with increased odds of adverse endpoints, including SpO2 < 93% and partial arterial pressure of oxygen less than 60 mm Hg on room air [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study also confirmed that severe/critical patients with respiratory rate ≥ 30 times/min and SpO2 of 93% or less in a resting state had higher total CT scores than ordinary COVID-19 patients [ 23 ]. Aalinezhad [ 24 ] and Osman[ 25 ] et al also reported higher chest CT score is inversely associated with O2 saturation. Furthermore, a multicenter cohort study demonstrated that consolidation in upper lungs on the initial chest CT of COVID-19 patients was associated with increased odds of adverse endpoints, including SpO2 < 93% and partial arterial pressure of oxygen less than 60 mm Hg on room air [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gemicioglu B. et al demonstrated a high SpO2 level of 92.57 ± 7.1% in COPD patients with COVID-19 infection [ 32 ]. At the same time, Aalinezhad M. et al has concluded that COPD was linked to more profound hypoxemia in patients with COVID-19-associated pneumonia (89.83 ± 8.02) [ 33 ]. Lee et al in the nationwide retrospective study in South Korea has shown an increased rate of ICU admission, mechanical ventilation and all-cause mortality in the COPD group [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies applied crude CT scoring systems. For example, Wang et al used 0:0%; 1:1–49%; 2:50–75%; 3: > 75%; range 0–3; global score 0–15 [ 16 ]; Hu et al used 0:0%; 1:1–25%; 2:26–50%; 3:51–75%; 4:76–100%; range 0–4; global score 0–20 [ 17 21 ]; Francone et al used 0:0%; 1: < 5%; 2:5–25%; 3:26–50%; 4:51–75%; 5: > 75%; range 0–5; global score 0–25 [ 22 , 23 ]; Zhao et al used 0:0%; 1: < 25%; 2:25–49%; 3:50–74%; 4: ≥ 75%; range 0–4; global score 0–24 [ 24 26 ]; Aalinezhad et al used another system (0:0%; 1: < 50%; 2: > 50%; range 0–2; global score 0–40) [ 27 , 28 ]. Similarly, Guillo et al used a scoring system of 0–10%, 11–25%, 26–50%, 51–75% and 76–100% ground-glass opacities and consolidation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the previous studies reporting that clinical characteristics including patient age and coexisting condition, immune status, body temperature and exposure history may be related to CT imaging in patients with viral pneumonia including SARS and COVID-19 [ 2 , 9 , 30 , 31 ]. In addition, Aalinezhad et al’s study also showed a significant inverse relationship between CT severity score and SpO 2 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%